High-throughput microfluidic imaging flow cytometry. (February 2019) - Stavrakis, Stavros; Holzner, Gregor; Choo, Jaebum; deMello, Andrew
Graphical abstract: Highlights: Microfluidic strategies for cell focusing are beneficial for the precise and accurate characterization of single cells in flow. Camera-based imaging flow cytometers provide ultra-high-throughput (>50 000 cells/s) analysis of cells within large populations. Photodetector-based imaging methods circumvent the speed limitations associated with traditional image sensors. Abstract : Recently, microfluidic-based flow cytometry platforms have been shown to be powerful tools for the manipulation and analysis of single cells and micron-sized particles in flow. That said, current microfluidic flow cytometers are limited in both their analytical throughput and spatial resolution, due to their reliance on single point interrogation schemes. Conversely, high-speed imaging techniques can be applied to a wide variety of problems in which analyte molecules are manipulated at high linear velocities. Such an approach allows a detailed visualization of dynamic events through acquisition of a series of image frames captured with high temporal and spatial resolution. Herein, we describe some of the most significant recent advances in the development of multi-parametric, optofluidic imaging flow cytometry for the enumeration of complex cellular populations.